Perbedaan Hasil Belajar Kimia Siswa Berbantuan Media Macromedia Flash dan Powerpoint Menggunakan Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division Pada Materi Koloid - Lista Adriani; Hafni Indriati Nasution (Universitas Negeri Medan, 2019)
This study aims to determine differences in student chemistry learning outcomes taught by Macromedia Flash and Powerpoint media using Student Teams Achievement Division cooperative learning models on colloidal subject matter. The population in this study were all students of class XI MIA Senior High School 2 Lubuk in 2017/2018 academic year. The sample used in this study was taken by random sampling of two classes. Each class consists of 30 students. Data collection techniques namely the test method. Data analysis technique in the form of a hypothesis test is a two-party t-test. Based on the results of the data requirements test, it is known that the results of the pretest and posttest results in the experimental class I and experiment II are normally distributed and homogeneous. As for the hypothesis test on student learning outcomes (posttest) tcount> t